2016
DOI: 10.1371/journal.pone.0148290
|View full text |Cite
|
Sign up to set email alerts
|

Complement System in the Pathogenesis of Benign Lymphoepithelial Lesions of the Lacrimal Gland

Abstract: ObjectiveWe aimed to examine the potential involvement of local complement system gene expression in the pathogenesis of benign lymphoepithelial lesions (BLEL) of the lacrimal gland.MethodsWe collected data from 9 consecutive pathologically confirmed patients with BLEL of the lacrimal gland and 9 cases with orbital cavernous hemangioma as a control group, and adopted whole genome microarray to screen complement system-related differential genes, followed by RT-PCR verification and in-depth enrichment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…This study had some limitations and the role of the mannosebinding lectin pathway in the pathogenesis of LGBLEL was not veri ed. Due to the di culty in obtaining normal lacrimal gland tissue, orbital CH was used as the control group, in line with previous studies [10] . In conclusion, the results of this and of previous studies indicate that both the classical pathway of the complement system and the bypass alternative pathway are involved in the pathogenesis of LGBLEL.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study had some limitations and the role of the mannosebinding lectin pathway in the pathogenesis of LGBLEL was not veri ed. Due to the di culty in obtaining normal lacrimal gland tissue, orbital CH was used as the control group, in line with previous studies [10] . In conclusion, the results of this and of previous studies indicate that both the classical pathway of the complement system and the bypass alternative pathway are involved in the pathogenesis of LGBLEL.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies used transcriptomics to preliminarily determine the involvement of the complement system in the pathogenesis of LGBLEL [10] . Transcriptomics analyzes organisms at the transcriptional level, including the regulation and function of genes at different stages of disease, while proteomics is a comprehensive and in-depth study of the proteome of disease and is used to screen key protein biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the gene expression profile between Cavernous Hemangioma (CH), a benign, non-infiltrative, slowly progressive vascular neoplasm of the orbit [ 30 , 31 ] and BLEL, some authors reported the involvement of T-cell receptor (TCR)-signaling pathway [ 32 ], Complement System [ 33 ] and B-cell receptor signaling pathways in the pathogenesis of BLEL [ 34 , 35 ], that confirmed the role played by the inflammatory process in the pathogenesis of BLEL. Here, we sought to identify the mediators of the inflammatory response and highlight their implication in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that complement mediated signaling pathways, T cell signaling pathways, and B cell signaling pathways are all involved in the pathogenesis of LGBLEL [1,7,8] . FcεRI is a high-affinity IgE receptor, which has been shown to be involved in type I hypersensitivities, such as allergic asthma [9] .…”
mentioning
confidence: 99%